AN EXPLORATION OF THE IMPACT OF ARTIFICIAL INTELLIGENCE ON CYBERSECURITY: THREATS AND OPPORTUNITIES - Hina Mehboob,; Rana Arbab Haider,; Ghias Akram Chairman,; Saira Rehman, (Spectrum of Engineering Sciences, 2025)
This study investigates the transformative impact of artificial intelligence on organizational cybersecurity capabilities through a mixed-methods research approach. Quantitative analysis of security metrics from 218 organizations across multiple sectors, complemented by qualitative insights from 47 cybersecurity professionals and technical evaluations of 14 AI-powered security solutions, reveals significant performance improvements associated with AI implementation. Organizations employing AI-powered security tools demonstrated substantial reductions in detection and response times (69.7% and 64.1% respectively), decreased security incidents (18.9%), and reduced successful breaches (44.7%). However, implementation success varies considerably across industry sectors and organization sizes, with financial services and larger organizations achieving the greatest benefits. Key implementation challenges include skills gaps, data quality issues, and integration complexity, while success factors encompass cross-functional collaboration, incremental implementation approaches, and effective human-AI collaboration models. The findings suggest that AI is fundamentally altering the cybersecurity landscape by augmenting human capabilities, enhancing threat detection accuracy, and accelerating response actions, though significant organizational and process adaptations are required to realize these benefits fully. The study provides a comprehensive framework for understanding AI's role in cybersecurity and practical guidance for organizations navigating this complex technological transformation.